Real-world cost-effectiveness of etonogestrel implants compared to long-term and short term reversible contraceptive methods in France. (4th July 2021) - Linet, Teddy; Lévy-Bachelot, Laurie; Farge, Gaëlle; Crespi, Simone; Yang, Joe Z.; Robert, Julien; Fabron, Cécile
Abstract: Background: To estimate the cost-effectiveness (CE) of etonogestrel implants compared to other long-term and short-term reversible contraceptive methods available in France. Research design and methods: A 6-year Markov model compared effectiveness between the implant and six other contraceptive methods in sexually active, not-pregnancy-seeking French females of reproductive age. Contraception efficacy, switch rates and outcomes were based on French current medical practice. Incremental CE ratios (ICERs) were calculated as incremental cost per unintended pregnancy (UP) avoided. Efficiency frontier was plotted to identify cost-effective methods. Uncertainty was explored through sensitivity analyses. Results: The implant was on the efficiency frontier along with combined oral contraceptive pill (COC) and copper IUD. Implant avoids between 0.75% and 3.53% additional UP per person-year compared to copper IUD and second generation COC, respectively, with an ICER of €2, 221 per UP avoided compared to copper IUD. For the 240, 000 French women currently using the implant, up to 8, 475 UPs and up to 1, 992 abortions may be prevented annually. Conclusion: With more unintended pregnancies avoided and comparable costs to copper IUD, the implant is a cost-effective option among long-term and short-term reversible contraceptive methods.